A comprehensive assay for nine major cytochrome P450 enzymes activities with 16 probe reactions on human liver microsomes by a single LC/MS/MS run to support reliable in vitro inhibitory drug–drug interaction evaluation. (2nd November 2015) - Peng, Ying; Wu, Hui; Zhang, Xueyuan; Zhang, Fengyi; Qi, Huanhuan; Zhong, Yunxi; Wang, Yu; Sang, Hua; Wang, Guangji; Sun, Jianguo
Abstract: 1. A comprehensive method for the simultaneous characterization of xenobiotic compound inhibition of nine major CYP enzymes in human liver microsomes was established by using 16 CYP-catalyzed reactions of 14 probe substrates with three cocktail incubation sets and a single LC/MS/MS analysis. 2. The three cocktail subgroups were developed to minimize the effects of organic solvents, polyunsaturated fatty acids and mutual substrate interactions: Group I was composed of tolbutamide (CYP2C9), S -mephenytoin (CYP2C19), testosterone (CYP3A4), dextromethorphan (CYP2D6); Group II was composed of nifedipine (CYP3A4), midazolam (CYP3A4), coumarin (CYP2A6), bupropion (CYP2B6), diclofenac (CYP2C9); Group III was composed of phenacetin (CYP1A2), chlorzoxazone (CYP2E1), omeprazole (CYP2C19 and CYP3A4), paclitaxel (CYP2C8), (+)-bufuralol (CYP2D6). In the case of CYP2C9, CYP2C19, CYP2D6 and CYP3A4, multiple probe substrates were used due to the phenomenon of multiple substrate-binding pockets and substrate-dependent inhibition. All probe metabolites were simultaneously analyzed with a polarity switching mode in a single LC/MS/MS run. 3. This method was validated against the single probe substrate assay using 12 well-characterized CYP inhibitors and two new entities (GT0918, MDV3100). The IC50 values of each inhibitor in the cocktail agreed well with that of the individual probe drug as well as with values reported in previous literatures.